New local and nonlocal soliton solutions of a nonlocal reverse space-time mKdV equation using improved Hirota bilinear method - Ahmad, Shabir; Saifullah, Sayed; Khan, Arshad; İnç, Mustafa (Elsevier, 2022)
Advanced mathematics has analyzed complex systems, a key area of research in nonlinear sciences, including fluid mechanics, the theory of solitons, hydrodynamics, optical fibers, and chaos theory. Nonlocal integrable mKdV equations could help understand dispersive waves in nonlinear and complex media. In this manuscript, we derive bright one and two soliton solutions for a nonlocal nonlinear integrable KdV equation using an improved Hirota bilinear method (HBM). We use MATLAB to visualize the obtained results in 3D space by choosing the appropriate parameter values. It is demonstrated that these solutions have novel characteristics that differ from those of the mKdV equation. (C0 2022 Elsevier B.V. All rights reserved.
Keywords: Hirota bilinear method; Periodic solitons; Nonlocal mKdV